The effect of ciplukan (Physalis angulate Linn.) leaf extract on the testicles of rats (Rattus norvegicus) exposed to heat - Annisa Nur Fitria Rahma; Sherina Lashita Candrakirana; Rimayanti Rimayanti; Tri Wahyu Suprayogi; Budi Utomo; Tatik Hernawati; Anwar Ma'ruf; Nove Hidajati; Kadek Rachmawati; Eka Pramyrtha Hestianah; Hani Plumeriastuti (Ovozoa: Journal of Animal Reproduction, 2024)
This study aims to determine the effect of administration of ciplukan (Physalis angulate Linn.) leaf extract on the variables of testicular weight, seminiferous tubules diameter, and spermatozoa plasma membrane integrity of rats (Rattus norvegicus) exposed to heat as model animals. Rats were divided randomly into five groups. In the NC group, rats were not exposed to heat and were only given 1% Na-CMC. In the PC, T1, T2, and T3 rats were exposed to heat followed by administration of 1% Na-CMC, 100, 200, and 400 mg/kg bw of ciplukan leaf extract (CLE) in 1% Na-CMC. Heat exposure at 40°C was conducted for 60 minutes every day for 21 days. On day-22, all rats were sacrificed for testicular evaluation. The results showed that all variables in the PC group were lower (p <0.05) than in the NC group. All variables in the T3 group were higher (p <0.05) than in the PC group. Testicular weight and spermatozoa plasma membrane integrity in the T3 group were not significantly different (p >0.05) from the NC group. However, the diameter of the seminiferous tubules in the T3 group were lower (p <0.05) than in the NC group. This study revealed that the administration of ciplukan leaf extract as an antioxidant increased testicular weight, seminiferous tubules diameter, and spermatozoa with intact plasma membrane in rats exposed to heat.